SLAP lesion and injury of the proximal portion of long head of biceps tendon in elite amateur wrestlers - Molnár, S.; Hunya, Z.; Pavlik, A.; Bozsik, A.; Shadgan, B.; Maffulli, N. (Indian Journal of Orthopaedics, 2020)
Background: Injuries to the proximal portion of the tendon of the long head of the biceps are challenging, and often only diagnosed at arthroscopy. However, it is important to be able to formulate a preoperative plan based on physical examination and imaging studies, so as to inform patients correctly, plan the likely procedure, and give indication to length and modalities of rehabilitation. Materials and Methods: Eleven elite wrestlers who suffered their injury between 2008 and 2018 were investigated retrospectively. We aimed to identify an association between the mechanism and the symptoms of the biceps-labral complex injury. Results: The injury was sustained at a mean age of 20.63 years, and most wrestlers were middle or light weight. All injuries occurred during shoulder movements in closed kinetic chain with the elbow extended, the forearm pronated and the shoulder slightly elevated. The surgical procedures performed were tenodesis in three wrestlers, reinsertion in seven wrestlers, and one tenotomy of the tendon of the long head of the biceps. The postoperative rehabilitation was shorter (1-3 month) in case of tenodesis or tenotomy, and markedly longer after reinsertion (6-9 months). Conclusions: Injuries to the proximal part of long head of biceps tendon are relatively frequent in elite wrestlers, reflecting the high functional demands imposed on the upper limb. Though necessitating surgery, in these athletes, such injuries are not career ending, and most of our elite athletes returned to high performance levels after surgery.